2019
DOI: 10.1093/jcbiol/ruz044
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of Haloniscus Chilton, 1920 (Isopoda: Oniscidea: Philosciidae), with description of four new species from threatened Great Artesian Basin springs in South Australia

Abstract: Recent surveys of Australian arid-zone groundwater ecosystems have uncovered considerable species diversity and extreme endemism for the oniscidean isopod genus Haloniscus Chilton, 1920. Phylogenetic and species delimitation analyses have recognised several distinct species from the Great Artesian Basin springs in South Australia, inspiring a morphological reassessment of the genus and examination of specimens from the iconic Lake Eyre and Dalhousie Springs. We present a revised diagnosis of Haloniscus, transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Overall, the exon capture methods and bioinformatics data processing approach used here have been effective in obtaining a large set of single-copy orthologous groups, successful bait design that enriches targeted loci from diverse Haloniscus and other more distantly related isopod species, and generating a large and informative phylogenomic dataset. While the final alignments employed for ML tree inference contained differing levels of missing data, the phylogenies revealed identical topologies and were largely consistent with previous taxonomic and phylogenetic research [28,30,66]. In contrast to previous studies, however, most of the phylogenetic relationships inferred here were fully resolved, showing maximal bootstrap support, particularly for internal branches, which provides further confidence in this approach.…”
Section: Plos Onesupporting
confidence: 86%
“…Overall, the exon capture methods and bioinformatics data processing approach used here have been effective in obtaining a large set of single-copy orthologous groups, successful bait design that enriches targeted loci from diverse Haloniscus and other more distantly related isopod species, and generating a large and informative phylogenomic dataset. While the final alignments employed for ML tree inference contained differing levels of missing data, the phylogenies revealed identical topologies and were largely consistent with previous taxonomic and phylogenetic research [28,30,66]. In contrast to previous studies, however, most of the phylogenetic relationships inferred here were fully resolved, showing maximal bootstrap support, particularly for internal branches, which provides further confidence in this approach.…”
Section: Plos Onesupporting
confidence: 86%
“…For eDNA metabarcoding to be an effective tool for biomonitoring, an accurate barcode reference library is required: a database containing DNA sequences annotated with taxonomic information such that new sequences may be referenced against it to determine the identity of the organism they originated from. For GAB spring taxa, much of existing publically available DNA sequence data corresponds to the mitochondrial cytochrome c oxidase subunit 1 (CO1) mitochondrial gene, limiting the ease of taxonomic identification of eDNA data represented by other genes or loci (i.e., nuclear or other mitochondrial genes, commonly 12S, 16S, or 18S rRNA) or for organisms lacking a mitochondrion such as bacteria (Page et al, 2007;King, 2009;Murphy et al, 2009;Guzik et al, 2012;Murphy et al, 2013;King et al, 2014;Murphy et al, 2015a;Guzik et al, 2019;Stringer et al, 2019). If eDNA metabarcoding were to be implemented as a biomonitoring tool in GAB springs, DNA sequencing for other barcoding genes would be required to establish robust and taxonomically accurate barcode reference libraries (Saccò et al, 2022).…”
Section: Improving Biodiversity Monitoring Methodsmentioning
confidence: 99%
“…Metrics calculated from only confident records are available in Supplementary File S2. We use the term "taxon richness" over "species richness" here as several taxa in the dataset are putative species based on morphological and/or molecular divergences per their respective taxonomic authorities (Greenslade, 1985;Murphy et al, 2009;Guzik et al, 2012Guzik et al, , 2019DeBoo et al, 2019;Stringer et al, 2019).…”
Section: Biodiversity Metrics and Community Compositionmentioning
confidence: 99%
“…(Rossini et al, 2018) subsequently increased this number to 52 across 154 SA spring groups in a synthesis on GAB spring endemics. These checklists have been supplemented by genetic studies of the taxa found in SA GAB springs such as crustaceans (Murphy et al, 2009, 2013, 2015; Guzik et al, 2012, 2019; Guzik & Murphy, 2013; Stringer et al, 2019), snails (Ponder et al, 1995; Murphy et al, 2012), beetles (DeBoo et al, 2019), spiders (Gotch et al, 2008), and microbes (Byers et al, 1998). Collating fundamental biodiversity information such as this and ensuring the data are accessible and usable is a first step towards future science-based decision making (i.e., FAIR).…”
Section: Introductionmentioning
confidence: 99%